A magnetic-field enriched surface-enhanced resonance Raman spectroscopy strategy towards the early diagnosis of malaria - Yuen, Clement (2013)
Early malaria diagnosis is important because malaria disease can develop into fatal illness within hours upon the appearance of the first symptom. The low concentration of the diagnosis biomarker, hemozoin, at the early stage of malaria disease makes early diagnosis difficult. In this paper, we present a magnetic field-enriched surface-enhanced resonance Raman spectroscopy (SERRS) strategy for the sensitive detection of β - hematin crystals, which is equivalent to hemozoin in the characteristics of Raman spectrum, by using magnetic nanoparticles. We observe several orders of magnitude enhancement in the SERRS signal of enriched β - hematin in comparison to the Raman signal of β - hematin in the cases of SERRS alone or magnetic enrichment alone, showing the great potential of this method towards early malaria diagnosis.